THE INFLUENCE OF THE THINK PAIR SHARE LEARNING MODEL IN ISLAMIC RELIGIOUS EDUCATION LESSONS TO INCREASE STUDENT LEARNING ACTIVITIES - Astika, Yuni; Ritonga, Supardi (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2024)
This research is motivated by the fact that religious education learning is still carried out conventionally, causing less than optimal learning pressure and low learning activity in participating in learning. This research aims to describe the influence of the Think Pair Share learning model in increasing the learning activity of class VII students in Islamic religious education subjects at SMP Negeiri 2 Bengkalis and the supporting or inhibiting factors. This type of research is experimental research with a quantitative approach. Observation, documentation, and tests are used to collect data. The data analysis technique used is descriptive analysis. The results of this research are the first, from the results of hypothesis testing using the Paired Simple T-Test test model, we obtained a significance result of 0.000 which is smaller and <0.05, so Ha is accepted in this research, meaning Ha is accepted in this research, meaning Ha accepted into this research. that there is a significant influence of the TPS (Think Pair Share) type learning model in increasing the learning activities of class VIII students in Islamic religious education subjects at SMP Negeri 2 Bengkalis. Then it can be seen from the test results that the experimental class obtained an average score of 80.31, which was greater than the control class which obtained an average score of 74.38. others, namely a non-conducive classroom atmosphere, time, and selection of discussion partners.